Pengaruh Good Corporate Governance Dan Struktur Modal Terhadap Kinerja Keuangan - Virda Susanti; Tries Ellia Sandari (Akuntansi, 2023)
This study aims to determine the effect of good corporate governance and capital structure on the financial performance of healthcare sector companies listed on the Indonesia Stock Exchange in 2017-2021. This study uses a quantitative approach with secondary data sources obtained from company financial reports through the IDX and IDN financials websites. The sample used was 8 companies in the healthcare sector using a purposive sampling method. The data analysis technique used SPSS 22 software. Based on the results of the study, it was shown that partially the board of directors indicators with a sig value of 0.503 > 0.05, t-count -0.677 and the board of directors was 0.389 > 0.05, t-count 0.389 had no effect on financial performance (ROA), while the audit committee indicator with a sig value of 0.007 <0.05, t-count -2.868 has an effect on ROA. Capital structure variable with DAR indicator with sig value of 0.324 > 0.05, t-count -1.002 and DER of 0.179 > 0.05, t-count 1.371 had no effect on financial performance (ROA). Simultaneously with a value of 0.016 <0.05, f-count 3.258 the variable good corporate governance and capital structure affect financial performance.